PREPARATION, CHARACTERIZATION AND THERMAL-DEGRADATION OF POLY P-(2,4-DICHLOROBENZYL)STYRENE - COSKUN, M; DEMIRELLI, K; OZDEMIR, E (Elsevier Sci Ltd, 1995)
Polystyrene has been alkylated by reaction with 2,4-dichlorobenzyl chloride in dichloromethane at -5 degrees C in presence of anhydrous aluminium chloride. The alkylated polystyrene has been characterized by IR and NMR spectroscopy. The chlorine content (26.7 wt%) shows that 97% of the styrene units have been alkylated. While the solubility parameter and density of the alkylated polymer are similar to those of polystyrenes, its glass transition temperature (83 degrees C), measured by DSC, is much lower than that of PS. The volatile products of thermal degradation of the alkylated polystyrene have been identified by gas chromatography and gas chromatography-mass spectrometry. 2,4-Dichlorobenzyl styrene has been observed among the oily products of degradation. Thermogravimetric studies show that the thermal stability of the alkylated PS is somewhat higher than that of PS.
Keywords: Halogenated Polymers; Polystyrene; Polymerization; Stability